Analysis of Rice Distribution in South Sumatera, Indonesia - Adam, Mohamad; Marwa, Taufiq; Azwardi, Azwardi; Thamrin, K.M. Husni; Bashir, Abdul (International Journal of Economics and Financial Issues, 2017)
This research investigates and determine the distribution of commodity rice in South Sumatera. Data are obtained from the primary data in 2016. The analysis method used is Descriptive Statistics, and Participatory Rural Appraisal (PRA) to determine the pattern of distribution of commodities of rice. The result in this research are, first, marketing distribution channels of rice in South Sumatera are still passed the long stage, first start from Manufacturers sold to distributor in the village, and then sold to Merchant Districts, then sold to Merchant District, then sold Large Distributor, next sold to retailers, and finally sold to the Consumer. Second, nominal terms, traders rice farmer is higher than distributor. But the ratio of rice trade margin (MPP) showed that MPP farmers was higher than MPP distributor. In general, these findings can be categorized efficiently. Keywords: Distribution Marketing, Rice, Marketing Margin. JEL Classifications: D3, L11, Q52